Comparison of Fracture Resistance and Failure Mode of Different Zirconia Abutments with Titanium Abutment - Ghasem Omati Shabestari; Marzieh Alikhasi; Reza Shabanpoor; Abbas Monzavi; Abbas Monzavi; Reza Shabanpoor; Marzieh Alikhasi; Ghasem Omati Shabestari (Tehran University of Medical Sciences, 2013)
Background and Aims: One of the decicive factors on the final esthetic results of implant treatment is theabutment material. Ceramic abutments are nowadays very popular in this regard. The purpose of this study was tocompare the fracture resistance of three zirconia abutments with titanium abutment.Materials and Methods: Four groups of abutments 4 recorded for each specimen. The data were analyzed using One-way ANOVA.Results: The mean values recorded for fracture resistance of different zirconia abutments varied between 426 to688 N; however, there was no significant differences among the groups